MiR-3606-3p inhibits systemic sclerosis through targeting TGF-β type II receptor. Issue 16 (18th August 2018) - Shi, Xiangguang; Liu, Qingmei; Li, Na; Tu, Wenzhen; Luo, Ruoyu; Mei, Xueqian; Ma, Yanyun; Xu, Weihong; Chu, Haiyan; Jiang, Shuai; Du, Zhimin; Zhao, Han; et al.
ABSTRACT: Systemic sclerosis (SSc) is a multisystemic fibrotic disease characterized by excessive collagen deposition and extracellular matrix synthesis. Though transforming growth factor-β (TGF-β) plays a fundamental role in the pathogenesis of SSc, the mechanism by which TGF-β signaling acts in SSc remains largely unclear. Here, we showed that TGF-β type II receptor (TGFBR2) was significantly upregulated in both human SSc dermal tissues and primary fibroblasts. In fibroblasts, siRNA-induced knockdown of TGFBR2 resulted in a reduction of p-SMAD2/3 levels and reduced production of type I collagen. Additionally, functional experiments revealed that downregulation of TGFBR2 yielded an anti-growth effect on fibroblasts through inhibiting cell cycle progression. Further studies showed that miR-3606-3p could directly target the 3′-UTR of TGFBR2 and significantly decrease the levels of both TGFBR2 mRNA and protein. Furthermore, SSc dermal tissues and primary fibroblasts contain significantly reduced amounts of miR-3606-3p, and the overexpression of miR-3606-3p in fibroblasts replicates the phenotype of TGFBR2 downregulation. Collectively, our findings demonstrated that increased TGFBR2 could be responsible for the hyperactive TGF-β signaling observed in SSc. Moreover, we identified a pivotal role for miR-3606-3p in SSc, which acts, at least partly, through the attenuation of TGF-β signaling via TGFBR2 repression, suggesting that the regulation of miR-3606-3p/TGFBR2 could be a promising therapeutic target that could improve the treatment strategy for fibrosis.